Exploring the Comfort Aspect of Self Eficacy for Sustainable Tourism in Pangururan District, Samosir Regency, Indonesia - Nurlisa Ginting (International Journal of Architecture and Urbanism, 2024)
Tourism initiatives that benefit both local populations and tourists contribute to long-term tourism growth. In order to build sustainable tourism, tourist locations must prioritize comfort. Comfort is extremely important in the tourist sector. It has a significant impact on travelers' decisions to visit touristic sites. Noise, cleanliness, traffic (both human and vehicle), the availability of public amenities, and local social contact all have an impact on comfort in the tourist industry. The purpose of this study is to determine the level of self-efficacy in the comfort zone of sustainable tourism in Indonesia's Pangururan District and Samosir Regency. A mixed method approach was used, involving the distribution of 268 questionnaires to visitors and residents, as well as interviews with representatives from the Samosir Regency. The results of the study show that self-efficacy comfort levels fall short of what is required for sustainable tourism. Reasonably high standards are met by the public facilities, which include parking spaces, roads, walkways, trash storage places, clean water, and information signs in both local and foreign languages. However, the degree of support for individuals with disabilities, waste disposal, and recycling activities falls short of the adequate standards. Thus, it is imperative to take more significant steps to ensure that all tourists can access and enjoy tourist destinations without any inconvenience. The recommendations for infrastructure and facility improvements are necessary to meet sustainable tourism standards and enhance the comfort aspect of tourism in the Pangururan District.